(untitled) (Pedagogy of Higher and Secondary Education, 2022)
Within the framework of the credit-module system of organization of educational process a student has a right to form an individual curriculum on the basis of alternative credits program units of preparation on speciality taking into account the set limitations. The sequence of disciplines is largely conditioned by a structurally-logical scheme - document which determines the relations of prioring between the credits modules. Limitations on disciplines of free choice are programmatically controlled at forming of individual curricula of students that facilitates the choice of disciplines of alternative part. Programming product is good for simplification of procedure of introduction of the credit-module system in higher educational establishment.